Biosynthesis of 3-Iodothyronamine (T(1)AM) Is Dependent on the Sodium-Iodide Symporter and Thyroperoxidase but Does Not Involve Extrathyroidal Metabolism of T(4) - Hackenmueller, Sarah A. (Endocrine Society, 2012)
3-Iodothyronamine (T(1)AM) is an endogenous thyroid hormone derivative with unknown biosynthetic origins. Structural similarities have led to the hypothesis that T(1)AM is an extrathyroidal metabolite of T(4). This study uses an isotope-labeled T(4) [heavy-T(4) (H-T(4))] that can be distinguished from endogenous T(4) by mass spectrometry, which allows metabolites to be identified based on the presence of this unique isotope signature. Endogenous T(1)AM levels depend upon thyroid status and decrease upon induction of hypothyroidism. However, in hypothyroid mice replaced with H-T(4), the isotope-labeled H-T(3) metabolite is detected, but no isotope-labeled T(1)AM is detected. These data suggest that T(1)AM is not an extrathyroidal metabolite of T(4), yet is produced by a process that requires the same biosynthetic factors necessary for T(4) synthesis.